Return on ideas : a practical guide to making innovation pay - Nichols, David, 1967- (Chichester, England ; Hoboken, NJ : John Wiley & Sons, 2007)
Return on Ideas is a practical guide to getting more from the resources you put into your innovation process. David Nichols clearly shows why current innovation funnel models stifle rather than encourage new ideas, and offers a new methodology, 'rocketing', to tackle the problem. The first book to look in detail at innovation as a business-driving imperative, Return on Ideas provides the tools, techniques and processes to actually upgrade the way you tackle innovation, illustrated with examples from innovative companies such as Yo! Sushi, Apple, Vodafone, Unilever, P & G, Danone, Amex and Ben &
Appendix: Rocketing toolkitIndex.
Print version record.
English.
John Wiley and Sons
Keywords: Product management; Brand name products; Diffusion of innovations; Diffusion of Innovation; Produits commerciaux -- Gestion; Produits de marque; Innovations -- Diffusion; BUSINESS & ECONOMICS -- Structural Adjustment; Brand name products; Diffusion of innovations; Product management